Regulators and effectors of small GTPases - Balch, William Edward; Der, Channing J.; Hall, Alan (Methods in enzymology, 2001)
Small GTPases play a key role in many aspects of contemporary cell biology: control of cell growth and differentiation; regulation of cell adhesion and cell movement; the organization of the actin cytoskeleton; and the regulation of intracellular vesicular transport. This volume and its companions (Volumes 255, 256, 257, and the forthcoming 325) cover all biochemical and biological assays currently in use for analyzing the role of small GTPases in these aspects of cell biology at the molecular level
Includes bibliographical references and indexes. - Print version record
Keywords: Electronic books